Experimental Study of the Performance of the Calpeda B Cm 20e Type Centrifugal Pump as a Practical Tool - Eldion Sinambela; Abdul Gafur; Burhan Hafid (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Centrifugal pumps are widely used in industrial applications and educational laboratories because of their simple construction, ease of operation, and ability to provide a stable flow rate. This study aims to analyze the performance of the CALPEDA BCM 20E centrifugal pump through experimental testing as a laboratory learning medium. In addition, the study develops a practical testing system by integrating transparent piping and a digital flow meter to improve the accuracy of flow rate measurements and enable direct observation of fluid flow. The research employs an experimental method by operating the pump under several operating conditions to obtain data on flow rate, total head, hydraulic power, shaft power, and pump efficiency. The collected data are analyzed using fundamental fluid mechanics equations and centrifugal pump performance characteristics and are presented in the form of tables, graphs, and performance curves. The developed laboratory equipment is expected to improve students' understanding of fluid flow phenomena and the relationship among flow rate, head, hydraulic power, and pump efficiency. The findings of this research are expected to provide useful information for evaluating centrifugal pump performance and support the development of more effective and interactive laboratory learning media.